ANALISIS TERHADAP PRAKTEK TERORISME ATAS NAMA JIHAD - Kasjim Salenda (Al Qalam, 2009)
Discourses on terrorism and jihad have been intensively discussed after September 11, 2001. Some argue that terrorism and jihad are correlated. In fact, terrorism and jihad substantially differ. Terrorism tends to be revolutionary and destructive that cause panics and fears, and it acts based on no clear principles, while jihad tends to improve human's safety and welfare personally or collectively, and the actions of it base on clear principles. Some Muslims, particularly radical Muslims, in which they commit terrorism as an actualization of jihad. This is due to internal and external factors. Internally, it is related to their limited understanding towards Islamic texts in which they use textual approach. Externally, socio cultural and political factors of Muslim community lead terrorists to commit terrorism.